2010
DOI: 10.5194/acp-10-11261-2010
|View full text |Cite
|
Sign up to set email alerts
|

Global modeling of organic aerosol: the importance of reactive nitrogen (NO<sub>x</sub> and NO<sub>3</sub>)

Abstract: Reactive nitrogen compounds, specifically NOx and NO3, likely influence global organic aerosol levels. To assess these interactions, GEOS-Chem, a chemical transport model, is updated to include improved biogenic emissions (following MEGAN v2.1/2.04), a new organic aerosol tracer lumping scheme, aerosol from nitrate radical (NO3) oxidation of isoprene, and NOx-dependent monoterpene and sesquiterpene aerosol yields. As a result of significant nighttime terpene emission… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
197
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 270 publications
(209 citation statements)
references
References 65 publications
10
197
0
2
Order By: Relevance
“…6). This suggests that isoprene OA formation may be only half of the value found by Kim et al (2015), implying that other sources such as terpenes may make more important contributions to OA (Pye et al, 2010(Pye et al, , 2015Xu et al, 2015).…”
Section: Implications For Surface Air Qualitymentioning
confidence: 82%
“…6). This suggests that isoprene OA formation may be only half of the value found by Kim et al (2015), implying that other sources such as terpenes may make more important contributions to OA (Pye et al, 2010(Pye et al, , 2015Xu et al, 2015).…”
Section: Implications For Surface Air Qualitymentioning
confidence: 82%
“…Fast Hg 0 oxidation in the polar spring boundary layer is simulated by specifying high BrO concentrations when conditions for temperature, sea ice cover, sunlight, and atmospheric stability are met . Monthly mean OA concentrations are archived from a separate v9-02 GEOS-Chem simulation including primary emissions from combustion and secondary production from biogenic and anthropogenic hydrocarbons (Pye et al, 2010). An evaluation of modeled OA against aircraft observations globally is presented in Heald et al (2011), which showed no systematic bias in remote environments but an underestimate of median concentrations in polluted regions.…”
Section: Atmospheric Chemistrymentioning
confidence: 99%
“…Current estimates are that human creation of reactive nitrogen (both oxidized and reduced nitrogen) increased by over an order of magnitude from ∼ 15 Tg N yr −1 to ∼ 187 Tg N yr −1 between 1860 and 2005 (Galloway et al, 2008). This increase is one of the primary causes of air pollution, contributing directly to the production of urban ozone and secondary organic aerosol (e.g., Carlton et al, 2010;Pye et al, 2010;Pinder et al, 2012;Rollins et al, 2012). The increase in NO x also results in an increase in the global background of OH (e.g., Wild et al, 2001).…”
Section: Introductionmentioning
confidence: 99%